Forecasts: Consumption, Production, and Behavioral Responses - Husnain F. Ahmad; Matthew Gibson; Fatiq Nadeem; Sanval Nasim; Arman Rezaee (Institute of Labor Economics (IZA), 2022)
Scarce information and human capital may make it difficult for residents of developing countries to produce accurate forecasts, limiting responses to uncertain future events like air pollution. We study two randomized interventions in Lahore, Pakistan: 1) provision of air pollution forecasts; 2) general training in forecasting. Both reduced subjects' own air pollution forecast errors; the training effect suggests that modest educational interventions can durably improve forecasting skills. Forecast receipt increased demand for protective masks and increased the responsiveness of outdoor time to pollution. Forecast recipients were willing to pay 60 percent of the cost of mobile internet for continued access.
Keywords: Q56; Q53; D84; D90; 330; pollution avoidance; training; forecasts; environmental information